(untitled) (ESMAT Magazine, 2025)
This study addresses the reflection on the (in)visibility of women with disabilities in the face of public and social policies regarding the confrontation of gender violence in the Brazilian reality. Since women with disabilities are (in)visible and excluded from the construction of society and in the main normative frameworks of laws that build actions to combat gender violence in international and Brazilian contexts. Therefore, the literature review tells us that these women have always been existing people of this modern society, past and present, being oppressed and violated by social markers of difference, from race, gender, social class, disabilities and others; and they are people constituted of rights and duties as well, as well highlighted by the Federal Constitution of 1988, which makes us equal in terms of civil, political and especially social rights to all Brazilians. In view of the exposed context of exclusion, silencing and (in)visibility of women with disabilities, the analytical tool of intersectionality allows us to present, why women with disabilities are (in)visibilized, and have their rights neglected, as well as why that their bodies are oppressed and violated in the patriarchal, sexist, sexist, ableist and modern capitalist society, but also intersectionality presents us with several paths with possibilities, for the process of inclusion and equity of these women in social life. The methodology that underlies this study is based on reviewing the collections of documents and laws, as well as the literature review and access to podcasts on YouTube on the subject in question.